Cropping sequence influenced crop yield, soil water, and soil properties in wheat-camelina cropping system - Eric Obeng; Augustine K. Obour; Nathan O. Nelson; Ignacio A. Ciampitti; Donghai Wang (Farming System)
Integrating camelina (Camelina sativa L. Crantz) into wheat (Triticum aestivum L.) -based cropping systems in the Great Plains Region of the United States could improve soil properties and overall system productivity. However, there is little information on crop yields and soil properties in dryland cropping systems with camelina rotation. This study investigated the effect of replacing fallow with camelina on crop yields, soil water content, and soil properties in dryland wheat-based cropping systems in western Kansas, United States, from 2013 to 2017. Treatments were four crop rotations, wheat-fallow (W–F), wheat-sorghum (Sorghum bicolor (L) Moench) -fallow (W–S–F), wheat-camelina (W–C), and wheat-sorghum-camelina (W–S–C) in a randomized complete block design with four replications. Results showed sorghum grain yield was unaffected by camelina in the crop rotation. Wheat grain yield was reduced by 15% when camelina replaced fallow in the rotation. Camelina yield was two-fold greater when planted after wheat (W–C) relative to the yield after sorghum (W–S–C). Increasing cropping intensification increased annualized yield compared to W–F. Soil water content was less in intensified crop rotations compared to rotations with fallow. Soil organic carbon varied among crop rotations and was least in W–F (1.4%). The W–S–C rotation had the greatest microbial biomass carbon, while microbial biomass nitrogen was least in W–C regardless of sampling time. Rotations including camelina had greater potentially mineralizable nitrogen. Increasing cropping intensity increased the proportion of larger water stable soil aggregates, while the less intensified system (W–F) had greater proportion of smaller water stable soil aggregates. Our findings suggest adding camelina to wheat-based crop rotations decreased wheat yields, but improved soil properties and increased the overall system productivity.